Pertentangan Hak-Hak dan Teologi Rekonsiliasi - Borgias M., Fransiskus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2005)
All human being has fundamental rights and duties. There appears possible conflict of rights and interests in the dynamics of social interaction, and possible conflict between individuals and community. This article tries to put forward a thesis that community of rights could be harmonized to each other. There are at least two ways to achieve this goal. First, the formation of consciousness of the significance of political-holiness. Secondly, pastoral formation for the spirituality of reconciliation. Both are necessary in order to avoid people from being frustrated because of being trapped in a “dirty” politics and state. And besides, we need spirituality of reconciliation as a source of new spirit and energy for people devastated by bloody conflicts. We are in need of peace gained through justice (opus iustitiae pax).